The Successful of Strengthening ASEAN Centrality Through the ASEAN Way - Purwanto, Adi Joko (Journal of Contemporary Sociological Issues, 2024)
Southeast Asia is a region with a strategic geographical location in global politics. History has proven that international political contestation occurred in this region from the era of colonialism at the end of the 16th century until no. This article explores how the Southeast Asian region is still a place of power rivalry and influence of major world powers such as China and the United States and, in the broader scope, the Indo-Pacific region. The research implemented Immanuel Kant's triangle of global politics and liberalism perspective to inquire into ASEAN countries' policy due to regional security and peacebuilding. It also uses literature study as a research method. The result indicates that ASEAN, established in 1967, has played a significant role in regional politics, especially in maintaining security and stability. The success of ASEAN is inseparable from the way ASEAN diplomacy with external partners by holding the principles and values believed by ASEAN member countries, known as the ASEAN Way. The values embodied in The ASEAN Way are vital to ASEAN's success Under The Indo-Pacific Strategy. Keywords: ASEAN, ASEAN Way, Indo-Pacific, Geo-Politic, Regionalism